A Think-Aloud Study of Novice Debugging - Whalley, Jacqueline; Settle, Amber; Luxton-Reilly, Andrew (Association for Computing Machinery (ACM), 2023)
Debugging is a core skill required by programmers, yet we know little about how to effectively teach the process of debugging. The challenges of learning debugging are compounded for novices who lack experience and are still learning the tools they need to program effectively. In this work, we report a case study in which we used a think-aloud protocol to gain insight into the behaviour of three students engaged in debugging tasks. Our qualitative analysis reveals a variety of helpful practices and barriers that limit the effectiveness of debugging. We observe that comprehension, evidence-based activities, and workflow practices all contribute to novice debugging success. Lack of sustained effort, precision, and methodical processes negatively impact debugging effectiveness. We anticipate that understanding how students engage in debugging tasks will aid future work to address ineffective behaviours and promote effective debugging activities.
Keywords: 3901 Curriculum and Pedagogy; 46 Information and Computing Sciences; 39 Education; 0806 Information Systems; 0899 Other Information and Computing Sciences; 1301 Education Systems; Education; 3901 Curriculum and pedagogy; 4608 Human-centred computing